2007
DOI: 10.1136/jmg.2007.050773
|View full text |Cite
|
Sign up to set email alerts
|

Gender-stratified analysis of DLG5 R30Q in 4707 patients with Crohn disease and 4973 controls from 12 Caucasian cohorts

Abstract: Background: DLG5 p.R30Q has been reported to be associated with Crohn disease (CD), but this association has not been replicated in most studies. A recent analysis of gender-stratified data from two case-control studies and two population cohorts found an association of DLG5 30Q with increased risk of CD in men but not in women and found differences between 30Q population frequencies for males and females. Male-female differences in population allele frequencies and male-specific risk could explain the difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 48 publications
1
28
1
2
Order By: Relevance
“…Similar results could not be replicated in a broad spectrum of subsequent studies [70][71][72][73]. Interestingly, presence of DLG5 R30Q was found to decrease the risk of developing CD specifically in women [74], whereas it increases the risk of developing CD in men [75]. This difference could be explained by the difference in male and female allele frequencies as demonstrated in several studies and it may account for the dilemma of reproducing the association of R30Q and CD.…”
Section: Dlg5contrasting
confidence: 60%
See 1 more Smart Citation
“…Similar results could not be replicated in a broad spectrum of subsequent studies [70][71][72][73]. Interestingly, presence of DLG5 R30Q was found to decrease the risk of developing CD specifically in women [74], whereas it increases the risk of developing CD in men [75]. This difference could be explained by the difference in male and female allele frequencies as demonstrated in several studies and it may account for the dilemma of reproducing the association of R30Q and CD.…”
Section: Dlg5contrasting
confidence: 60%
“…This difference could be explained by the difference in male and female allele frequencies as demonstrated in several studies and it may account for the dilemma of reproducing the association of R30Q and CD. Contrasting are the findings from a study by Browning et al, in which in a population of 4707 CD patients no difference in male and female allele frequencies could be demonstrated [74]. In a Hungarian study the 113A allele was shown to be associated with steroid resistance [76].…”
Section: Dlg5mentioning
confidence: 73%
“…Recently, Biank et al, reported that R30Q is a female-specific protective factor in pediatric CD [37]. A larger gender-stratified meta-analysis with 4707 CD patients and 4973 controls showed an association of 30Q with decreased risk of CD in females [35]. These observations raise very interesting questions including what is the "gender factor" and how does it affect IBD development?…”
Section: Discussionmentioning
confidence: 99%
“…Friedrichs et al, found a male-specific association of the R30Q variant with CD, with no association of the R30Q variant with women, nor with the entire sample of men and women [27]. However, the association of the R30Q variant with IBD failed to be replicated by several other groups with samples from several different countries, including Germany, Scotland, Belgium, and Hungary [28][29][30][31][32][33][34][35][36]. A US based population of IBD patients has been also studied [17,37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 29.6% of DEFEB1 20A carriers were antiglycan positive compared to 46% positivity in non-carriers (P < 0.038). However, no association of antiglycan positivity was found with either DEFEB1 G52A variant or DLG5 (R30Q), although both were shown to be associated with increased risk for CD [53,54] . Furthermore, in contrast to other reports [32,51] , no gene dosage effect was observed on any of the antiglycan antibodies.…”
Section: "New" Serological Ibd Biomarkersmentioning
confidence: 87%